The Quantification of Structural Reforms: Taking Stock of the Results for OECD and Non-OECD Countries - Balazs Egert (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper summarises earlier OECD work aimed at quantifying the impact of structural reforms on economic outcomes. It overviews i.) insights obtained for the linear relationships linking policies and economic outcomes (including multi-factor productivity, capital deepening and employment) for an almost complete set of OECD countries, ii.) non-linear results on how policies interact with each other in OECD countries, and iii.) results extended for emerging-market economies looking at whether policy effects vary across countries depending on the level of economic development and whether institutions have an influence on economic outcomes. The paper lists of policies and institutions that could be used to quantify the effect of reforms. It also gives some guidance on how to quantify reforms in OECD and non-OECD countries. It provides mid-point estimates of the long-run effects on per capita income levels through the three supply-side channels. Finally, it raises the issue of estimation and model uncertainty.
Keywords: D24; E17; E22; E24; J08; 330; structural reform; product and labour market regulation; institutions; productivity; investment; employment; OECD; emerging market